Nanocrystalline silicon (nc-Si:H) and amorphous silicon (a-Si:H)based thin-film multijunction solar cell - Shahzad Hussain; Haris Mehmood; Ghulam Ali (Universiti Kebangsaan Malaysia, 2014)
A novel thin-film multijunction solar cell based on nanocrystalline silicon (nc-Si:H) is presented in this paper. Existing thin-film double junction solar cells are based on amorphous silicon carbide (aSiC:H) and amorphous silicon layers. Such solar cells have limited efficiency due to lower absorption and poor charge transport properties of the a-SiC:H layer. These solar cells have maximum achieved efficiency of about 8.8%. In this work, a-SiC:H has been replaced with nc-Si:H layer and the double junction solar cell has been redesigned. The proposed structure has been simulated with Silvaco TCAD (ATLAS). The simulated results indicated a step increase in the performance of the solar cell with open circuit voltage Voc=2.096 V and efficiency η = 10.2%. It was proven that the nc-Si:H is a suitable material for the development of an efficient thin film multijunction solar cell.